Case Report of Concurrent Trigeminal Neuralgia and Glossopharyngeal Neuralgia - Chang Min Shin; Hyun Seob Park; Geun Mo Kim; Kyung Won Ha; Young Hun Lee; Shin Young Kim; Jong Cheol Seo; Hyun Min Yoon; Cheol Hong Kim (MEDrang Inc., 2024)
This study presents the first case of concurrent trigeminal neuralgia (TN) and glossopharyngeal neuralgia (GPN) that was improved with integrated Korean and Western medicine. The patient was admitted to Dong-Eui University Korean Medicine Hospital from June 11, 2024, to June 22, 2024, and was treated twice in the outpatient department. During the clinic period, the patient received Korean (acupuncture, pharmacopuncture, acupotomy, temporomandibular joint balancing therapy, and herbal medicine) and Western medicine treatment. Visual analog scale (VAS) and EQ-5D-5L were used to measure pain and discomfort. After treatment, the VAS pain level decreased from 7 to 0. On the EQ-5D-5L, the usual activity level decreased from 3 to 1, and the pain/discomfort level decreased from 4 to 1. Although these findings present the applicability and effectiveness of integrated Korean medicine in the treatment of TN and GPN, more studies are needed to confirm the efficacy.